Development of Saturated Fat Replacers: Conventional and Nano-Emulsions Stabilised by Lecithin and Hydroxylpropyl Methylcellulose - Jansuda Kampa; Richard Frazier; Julia Rodriguez-Garcia (Foods, 2022)
The combination of two emulsifiers, lecithin and hydroxypropyl methylcellulose (HPMC), into emulsions is an interesting strategy to design fat replacers in food matrices. The objective of this study was to investigate the effect of HPMC type and concentration on the formation, stability, and microstructure of conventional emulsions and nanoemulsions. Two different types of HPMC with low and high content of methyl and hydroxypropyl groups (HPMC-L and HPMC-H) were evaluated. The results showed that the molecular structure and concentration of HPMC play a major role in the viscoelastic behaviour, the gelation temperature, and the strength of gel formed. The firmness and work of shear of HPMC solutions increased significantly (p < 0.05) with increasing concentration. HPMC-L illustrated a more stable gel structure than the HPMC-H solution. Nanoemulsions showed lower moduli values, firmness, and work of shear than conventional emulsions due to the influence of high-pressure homogenization. A combination of lecithin and HPMC improved the physical and lipid oxidative stability of the emulsions, presenting a lower creaming index and thiobarbituric acid reactive substances (TBARS). In conclusion, HPMC-L at 2% w/w could be a suitable type and concentration combined with lecithin to formulate a saturated fat replacer that could mimic butter technological performance during food manufacturing operations.